PENGARUH PENEGAKAN PERATURAN, SISTEM KOMPENSASI, KETAATAN ATURAN AKUNTANSI DAN MORALITAS APARAT TERHADAP KECENDERUNGAN KECURANGAN AKUTANSI DENGAN PERILAKU TIDAK ETIS SEBAGAI VARIABEL INTERVENING SERTA PENGARUHNYA TERHADAP KINERJA INSTANSI PEMERINTAH (Stud - Tiffany Pratiwi; Emrinaldi Nur Dp; Rofika ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to analyze the direct effect of rule enforcement, compensation system, compliance of accounting rules and morality of apparatus toward tendency of accounting fraud and the direct effect of rule enforcement, compensation system, compliance of accounting rules and morality of apparatus toward unethical behavior and indirect effect of rule enforcement, compensation system, compliance of accounting rules and morality of apparatus toward tendency of accounting fraud which is mediated by unethical behavior and the direct effect of tendency of accounting fraud toward perfomance of government agencies. This study was conducted at 27 departments in Pekanbaru with 75 respondents. The data were analyzed by using PLS (Partial Least Square) analysis technique, while the method of determining the sample is by using purposive sampling method. The result shows that rule enforcement and morality of apparatus have direct influence toward tendency of accounting fraud. Nonetheless, compensation system and compliance of accounting rules variable do not have influence toward tendency of accounting fraud. The influence of compensation system, compliance of accounting rules and morality of apparatus was significantly affecting the unetichal behavior, but rule enforcement variable does not have influence toward unethical behavior. The influence of compensation system, compliance of accounting rules and morality of apparatus was significantly affecting the tendency of accounting fraud through unethical behavior. But, rule enforcement does not have significantly affecting to tendency of accounting fraud through unethical behavior.Keywords: tendency of accounting fraud, unethical behavior and PLS (Partial Least Square)